Study of visible light modulation based on magneto-optical thin films and dynamically tunable all dielectric metasurface embedded in nematic liquid crystal - Sun, Ming-Yu (2019)
The study of visible light modulators development has been intensively focused for advanced applications. Magneto-optical SLM (MO-SLM) and active all dielectric metasurface show outstanding performance in efficient visible light modulation. Large perpendicular magnetization anisotropy (PMA) of 480 emu/cm3 and a 0.5o polarization rotation magneto-optical Kerr effect (MOKE) was obtained in 60 nm thin MnBi layer. Oxidation effect was presented by magnetic measurements between a 14-day interval exposure in ambient environment. A dramatic enhancement of Kerr signal can be expected by introducing a layer of dielectric TiO2 layer (0.86o to 9.5o at 633 nm) based on the numerical simulation. In the meantime, wide range shift in spectra (close to 20 nm around the resonance  ~ 670 nm) and the 1.5 PI phase shift is obtained in the sample with a 1.5 um thin layer LC and drivable under a small voltage below 8 V. TiO2 metasurface of nano cylinders was fabricated by a series of standard process of e-beam lithography. Strong surface anchoring effect is observed with a large in-plane LC alignment deviation above PHI = 30o with respect to the preset LC photoalignment or rubbing alignment.